Strategic procurement's impact on organisations and prospects for multi-disciplinary research - Jeeva, Ananda (IEEE Intelligent Transport Systems Society (IEEE/ITSS), 2008)
Procurement and Supply Management strategies are becoming more vital in organisational strategic plans. Also there is an increase of demand and recognition for Chief Procurement Officers in large MNCs. Dr Jeeva will introduce the concept of procurement and supply management, and how the various schools and faculties can conduct multi-disciplinary research. The presentation will also look at some common theories and how they fit into the research context. This presentation intends to increase the awareness of the concepts of procurement and supply management. The understanding of procurement and supply concepts can lead to multi-disciplinary research between different faculties and schools. The presentation will also provide possible areas of multi-disciplinary areas of research between Procurement and: Law, Marketing, IT, IS, HRM, Engineering, Sciences, Agriculture andAccounting. This presentation encourages the formulation of the concept of procurement and supply into their areas of specialisation.